A systematic review and meta-analysis of cross-reactivity of antibodies induced by H7 influenza vaccine. Issue 2 (1st February 2020) - Gou, Xiaoqin; Wu, Xiaoxue; Shi, Yu; Zhang, Ke; Huang, Junqiong
ABSTRACT: Inoculation with vaccine is the major intervention currently used to prevent influenza infections. However, it will be a challenge to produce and implement a new vaccine when a novel highly pathogenic influenza virus emerges in humans as significant infections. H7 subtype influenza viruses have similar epitopes on hemagglutinin, which can induce cross-reactive antibodies. In this study, a meta-analysis of the cross-reactivity of antibodies induced by one H7 subtype influenza vaccine against other H7 subtypes was performed. Database search was conducted in PubMed, Cochrane Library, EMBASE, MEDLINE, Chinese Biological Medicine Database (CBM), and Wanfang. A total of 9 articles comprising 811 human subjects were included in this meta-analysis. All assessed H7 influenza vaccines induced vaccine strain-specific protective antibodies [seroconversion rate (SCR) = 0.74, 95% CI (0.65, 0.82); seroprotection rate (SPR) = 0.81, 95% CI (0.78, 0.83)]. All H7 influenza virus monovalent vaccines exhibited cross-reactivity tested by hemagglutinin inhibition test (HI), microneutralization test (MN) and immunosorbent assay (ELISA) to other H7 subtype viruses. H7N1, H7N3, H7N7, and H7N9 vaccines elicited cross-reactive antibodies against other H7 subtype influenza viruses [SCR = 0.66, 95% CI (0.50, 0.82); SPR = 0.79, 95% CI (0.67, 0.91)]. The pooled SCR (95%CI) of cross-reactivity of H7N1 and H7N3 vaccines were 0.88 (0.85, 0.91) and 0.40 (0.26, 0.54), respectively. The consolidated SPR (95%CI) of H7N1 and H7N7 vaccines were 0.89 (0.86, 0.92) and 0.93 (0.81, 1.06). All H7 vaccines induced cross-reactive antibodies against H7N9 viruses [SCR = 0.69, 95% CI (0.52, 0.86); SPR = 0.85, 95% CI (0.76, 0.94)]. H7 vaccines can be used to limit influenza infection when a new highly pathogenic H7 virus appears.